Fungsi Pengorganisasian dan Pelaksanaan Keuangan Puskesmas Berstatus Badan Layanan Umum Daerah - Firdhausy, Hima Sakina; Suryawati, Chriswardani; Harto, Puji (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2021)
Bergas Public Health Center as a PPK-BLUD unit was required to change traditional financial management methods into performance-based budgeting. The utilization of the budget from the APBD, BOK, and BLUD funds had reached more than 90%, but the achievement of SPM had not been maximal. This study aimed to analyze the functions of financial organization and implementation at the Bergas Public Health Center with PPK-BLUD status. This research used qualitative methods with a case study approach. Data collection techniques throughed in-depth interviews with triangulation of sources to test the validity of the data. The research informants were 15 respondents who were selected by purposive sampling. The research was carried out from March to August 2020. The results of the research on the organizing function showed that there were problems with coordination with activity executing officials, cooperation between program holders was still lacking, and the mindset of the implementer was not performance-based budgeting. In the implementation function, it was found that there were difficulties in managing accrual-based finance, BLUD funds had not been used for innovation in achieving SPM, SPI had not been implemented, and monitoring implementation had not been integrated regarding the absorption of performance-based budgets. The study concluded that the function of organizing and implementing finance had been running but had not fulfilled the SPM due to several obstacles. Keywords: Organizing, Implementation, Puskesmas Finance, BLUD